Secure message propagation protocols for IoVs communication components. (March 2020) - Vasudev, Harsha; Das, Debasis; Vasilakos, Athanasios V
Abstract: With the development of Internet of Vehicles (IoVs), the smart transportation field has achieved a lot of attention by providing a wide variety of benefits, such as enhanced road safety, reduced traffic congestion, traveler safety, and less pollution. It made the concept of 'intelligence on wheels' into a real one. However, the highly dynamic nature of vehicles and insecure channels are the significant challenges in an IoV environment. In the existing researches, secure and lightweight protocols for the IoVs communication components are missing. In this paper, we design secure and lightweight communication protocols for different components of IoVs, such as V2V (Vehicle-to-Vehicle), V2P (Vehicle-to-Portable Device), V2R (Vehicle-to-Road Side Unit), V2I (Vehicle-to-Infrastructure), and V2S (Vehicle-to-Sensor). We have done in-depth security analysis to ensure the resistant power against different strong attacks. Moreover, we have implemented the protocols on a Desktop Computer and Raspberry Pi. From the results, it is observed that the proposed protocols perform well in the perspectives of communication, storage, computation, and battery consumption than other competitive protocols.